The Impact of Workplace Stress on Employee Productivity: A Study at FamilyMart Malaysia - Oh Zi Jian; Nur Alia Natasya Binti Zulkifli; Nur Alia Syafiqah Binti Salim; Nur Aliah Safia Binti Zakie; Nur Alya Amani Binti Mohamad Zawawi; Harshita Gupta; Priyanshi Ramani; Daisy Mui Hung Kee (Journal of The Community Development in Asia, 2026)
This study examines the impact of workplace stress on employee productivity among frontline employees at FamilyMart Malaysia, a rapidly expanding convenience-store chain operating in a high-demand retail environment. Despite extensive research on workplace stress, empirical evidence within Malaysia’s convenience-store sector remains limited. Using a quantitative cross-sectional design, data were collected from 57 current and former FamilyMart employees through an online survey. The findings reveal that workplace stress, particularly workload pressure and customer-related demands, significantly reduces employee productivity by impairing concentration, motivation, and task accuracy. Regression analysis confirms that workplace stress is a significant predictor of reduced productivity, while emotional exhaustion plays a mediating role in this relationship. The study highlights workload pressure as the most dominant stressor affecting performance. These findings underscore the importance of implementing effective staffing strategies, supportive work practices, and employee well-being initiatives to enhance productivity and sustain service quality in fast-paced retail operations.